Exploring potential of bacterial endophytes in disease management of horticultural crops (Current Horticulture, 2024)
The endophytes are facultative or obligate symbiotic microorganisms, living in apparently healthy internal plant tissues, without causing disease in the host. Bacterial endophytes are found in a diverse group of plants including many horticultural crops, viz. fruits, flowers and medicinal plants. They harbour diverse group of bacterial endophytes including members of Pseudomonads, Bacillus and Streptomyces, which have been found successful against many phytopathogenic fungi and bacteria. Endophytes can suppress diseases through various mechanisms, viz. antibiosis, competion, lysis, siderophore production, enhanced host defense etc. Many Actinobacteria produce metabolites with antimicrobial activity which can be explored as a potential alternative to chemical in plant disease management. Moreover, bacterial endophytes have been reported to play a crucial role in bioremediation of organic and inorganic pollutants and promoting plant growth through nutrient enhanced nutrient uptake.
Keywords: Bacterial endophytes; Bioremediation; Disease management; Horticultural crops; Prudent option